Autonomic computing - Murch, Richard (On demand series., 2004)
This book introduces Autonomic Computing. This concept is a cornerstone of IBM's strategic initiative, and it offers great promise because autonomic computing systems have the ability to manage themselves and dynamically adapt to change in accordance with evolving or dynamic business policies and objectives. The term "autonomic" comes from the autonomic nervous system, which controls many organs and muscles in the human body. These systems can perform management activities based on situations they observe or sense in the IT environment. Rather than IT professionals initiating management activities, The system observes something about itself and acts accordingly. This allows the IT professional to focus on high-value tasks while the technology manages the more mundane operations. This book explains how this can be made to happen And The changes that need to be made to make it happen.